Perhitungan Harga Pokok Produksi Pada Usaha Peternakan Ayam Pedaging M.Yatim Desa Suka Datang Kecamatan Curup Utara - Adrianti, Viona; Paddery, Paddery; Feri, Feri (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This researcher aims to find out what appropriate method is applied by the M. Yatim Broiler Chicken Farm in Suka Datang Village, North Curup District. The analysis used in this research is a quantitative descriptive analysis method. The results of the research show that in the recapitulation of the number of broiler chickens of 23,200 during the 2023 harvest period, namely February to December, the results of calculating the cost of production at the M. Yatim broiler chicken farm, Suka Datang Village, North Curup District, are different, each method is different, The method used is full costing, obtaining Rp. 1,167,930,100 with a cost of production per unit of 50,342, while the variable costing method obtained 1,164,704,100 with a cost price per unit of 50,203 and the Activity Based Costing (ABC) method obtained 1,168,154,100 with a cost price per unit of 50,351.